Rubbish, Recycling and Religion: Indonesia’s Plastic Waste Crisis and the Case of Rumah Kompos in Ubud, Bali (International Journal of Interreligious and Intercultural Studies, 2020)
Indonesia is the second largest global source of marine plastic after China. Plastic waste, together with toxic smoke from extensive unregulated rubbish burning in homes and businesses, are grave public health threats in Indonesia. This paper presents a case study in Ubud, Bali of a community-based recycling and waste sorting project - Rumah Kompos –which demonstrates the potential of religious wisdom and belief to contribute to help solve Indonesia’s waste problem. The cultural role of religions in the case study is part of a larger Indonesian, and world religions, phenomenon in which churches, mosques and temples, and faith-based schools (and in Indonesia Islamic boarding schools or pesantren) have made efforts to sponsor pro-environmental behaviours at local community level. The paper also recalls the relevance of anthropological studies of religion, especially Mary Douglas’ classic study Purity and Danger, in understanding the connected genealogies of waste and religion. Douglas theorises that identification and regulation of hazardous and ‘polluting’ practices, concerning bodily fluids, food, clothing, housing, habitable land, potable water and sexual relationships was central to the social role of traditional religions. The disturbance to this long-established function of religion occasioned by the speed and scale of adoption of modern technological innovations, and of a modern ‘consumer lifestyle’, points to an under-studied dialectic between religion and waste which, in a nation as religiously active as Indonesia, ought to be included in both the conceptualisation of, and policy-making concerning, plastic and waste management.